Physical Properties of Selected Fruit Fibre and Pomace in the Context of Their Sustainable Use for Food Applications - Anna Pakulska; Ludwika Kawecka; Sabina Galus (Applied Sciences)
Pomace, a waste product, generates a huge problem in the fruit and vegetable industry. Numerous studies prove that pomace and fibre are valuable sources of many nutrients. Due to their properties, their popularity is growing in many industries. Water vapour isotherms and kinetics were determined for selected fruit fibre and pomace. The activity and water content, colour, apparent and bulk density, and material structure were also investigated. In addition, the thermal stability of the tested fibres and pomace was examined. Fibre and pomace from chokeberries, apples and currants were used in the research. The determined kinetic curves proved that apple fibre absorbed more water vapour. The isotherms were found to have a shape characteristic of type III sorption isotherms. The Guggenheim–Anderson–de Boer model (GAB) described experimental data for sorption isotherms well (taking an RMS value of less than 10% as a good fit of the model to the sorption data). Thermogravimetric analysis showed good thermal stability, and all analysed fruit fibre and pomace showed similar behaviour in the three main stages of weight loss. The results suggest that the analysed waste materials can be used for different applications, including flour replacements for food products or filling materials in edible packaging films.